ДОСЛІДЖЕННЯ ЕНЕРГОЕФЕКТИВНИХ РЕЖИМІВ РОБОТИ БАГАТОДВИГУННОГО СТРІЧКОВОГО КОНВЕЄРА - Печеник, М.В.; Бур’ян , С.О.; Наумчук , Л.М. (Інститут електродинаміки НАН України, Київ, 2016)
Рresents  mathematical model of 6-mass electromechanical system describing the motion of the conveyor belt with multimotor electric drive. The results of studies energy losses in the engines of main conveyor belt with the location of the two drive motors in the main and one in the tail section with the changing speed load torque. Is shown character of the change of energy efficiency depending on the load of the conveyor belt.  References 3, figures 2.